Argument Evaluation Contest Results - Jonathan E. Adler (Informal Logic, 1991)
In Vol. XI, No.1, this journal announced an argument analysis contest. Two eminent colleagues agreed to serve as judges-Professor Henry W. Johnstone, Jr. and Professor Michael Scriven. In short order, four entries were received and sent off to the judges, who had no knowledge of the contestants' identities, and in due course the judges' verdicts were delivered. Immediately below we have reproduced the argument which was to be analyzed, along with the rules of the contest, followed by the four entries. Thereafter we present the judges' rulings.